Nuclearity Control for Efficient Thermally Activated Delayed Fluorescence in a Cuicomplex and Its Halogen-Bridged Dimer - Lemus-Chavez, L; Lemus-Chavez, L; Aravena-Ponce, D; Aravena-Ponce, D; Arce-Ortega, P; Arce-Ortega, P; Llanos-Silva, L; Llanos-Silva, L (American Chemical Society, 2021)
We report on the thermally activated delayed fluorescence (TADF) properties of a novel iodine-bridged CuI dimeric complex and its structurally related monomer. The chemical environment around the copper centers is identical in both complexes, providing a clean comparison to understand the effect of nuclearity in CuI emitters. Efficient room-temperature TADF (≈80% of the total emission) is observed in both compounds. Similar singlet-triplet splittings were found for the monomer and the dimer (554 and 583 cm-1, respectively), while the dimer triplet lifetime (90.0 μs) was longer than that of the monomer (46.0 μs). Experimental findings were rationalized by time-dependent density functional theory and complete active space self-consistent field calculations, identifying key structural factors determining TADF properties such as the key role of iodine in spin-orbit coupling mixing and the importance of near degeneracies in donor and acceptor orbitals for promoting state mixing. Unavoidable modifications associated with a change in nuclearity (e.g. intermolecular interactions, molecular charge, or modification of some binding motifs) can be also designed to promote TADF performance. © 2021 American Chemical Society.